Gastrointestinal endoscopy - Silverstain, Fred E (Mosby-Wolfe, 1997)
The book provides comprehensive coverage of the normal appearance of the gastrointestinal tract, normal variants, and diseases of the esophagus, stomach, small bowel, biliary tree, pancreas, papilla of Vater, colon, and rectum. It concludes over 2000 illustrations, including 200 new endoscopic images, 40 new artworks, and 20